Combinatory composition. A procedure for fostering motivation and artistic creativity in compulsory secondary education - Ortega Cubero, Inés (Pulso. Revista de educación, 2012)
This article describes a project designed for first-year secondary school students. The idea stems from previous research on the work of the Spanish sculptor Ángel Ferrant, who was not just an important avant garde sculptor but also one of the most relevant theorists and pedagogues in the teaching of Art in Spain. Our students work, created through the use of Ferrants meticulously designed didactic games, is governed by spontaneity, imagination and aesthetic self-satisfaction. This study shows promise for both classroom and research work.